2012
DOI: 10.5513/jcea01/13.3.1064
|View full text |Cite
|
Sign up to set email alerts
|

Comparsion of production performance of two genetic groups of turkeys reared in the Semi-intensive system

Abstract: Production results were compared for two groups of turkeys reared in semi-intensive system. The material included 40 primitive turkeys of the light type and 40 heavy hybrids of the Big-6 line (commercial flock). Females was raised to 14 and males to 22 weeks of life. During the rearing, body weight (g) was controlled individually and feed intake (g) was monitored in groups, in weekly intervals. Significantly higher body weight values (P ≤ 0.01) were reported in both females (8806 g) and males Big-6 (23593 g), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The nutritional value of poultry meat, its high protein content, and low fat content as well as its flavor make it attractive to consumers, who increasingly declare their preference for meat of chickens that have been produced in the system taking the greatest possible care of birds' welfare (Damaziak, Michalczuk, & Kurek, 2012;Marcinkowska-Lesiak et al, 2016;Michalczuk, Łukasiewicz, Zdanowska-Sąsiadek, & Niemiec, 2014;Popova, Ignatova, Petkov, & Stanišić, 2016;Puchała, Krawczyk, Sokołowicz, & Utnik-Banaś, 2015). Studies have shown that more than half of Britons polled assessed the animals' welfare as very important, and more than 70% of the surveyed citizens of the United States reported concern about the welfare of farm animals (Norwood & Lusk, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional value of poultry meat, its high protein content, and low fat content as well as its flavor make it attractive to consumers, who increasingly declare their preference for meat of chickens that have been produced in the system taking the greatest possible care of birds' welfare (Damaziak, Michalczuk, & Kurek, 2012;Marcinkowska-Lesiak et al, 2016;Michalczuk, Łukasiewicz, Zdanowska-Sąsiadek, & Niemiec, 2014;Popova, Ignatova, Petkov, & Stanišić, 2016;Puchała, Krawczyk, Sokołowicz, & Utnik-Banaś, 2015). Studies have shown that more than half of Britons polled assessed the animals' welfare as very important, and more than 70% of the surveyed citizens of the United States reported concern about the welfare of farm animals (Norwood & Lusk, 2011).…”
Section: Introductionmentioning
confidence: 99%